Implementation of the Family Hope Program in Improving the Living Standards of Early Childhood in Wonokusumo Village, Surabaya City - Ivani, Ahmad Yusril; Wibawani, Sri (ARISTO, 2025)
The aim of this research is to determine and describe the implementation of the Family Hope Program in improving the standard of living of young children in Wonokusumo Village, Surabaya City. The research method used is qualitative descriptive research. Data collection techniques use interviews, observation and documentation. The technique for determining informants is purposive sampling analysis and snowball sampling. The data analysis technique uses interactive model data analysis developed by Miles & Huberman, namely Data Collection, Data Condensation, Data Presentation, and Conclusion Drawing and Verification, according to the research focus based on policy implementation theory according to Charles O Jones with three indicators, (1) Organization (2) Interpretation (3) Application. The results of the research are, (1) the organization, policy implementers understand what they are doing in accordance with their main duties and functions, (2) Interpretation, policy implementers refer to related regulations, namely Minister of Social Affairs regulation number 1 of 2018, and guidelines for implementing the Family Hope Program. They have carried out activities in accordance with what is written in the regulations, the procedures for implementing each activity have also been carried out appropriately by the policy implementers. (3) application, the program targets also understand what they are doing, such as participating in mentoring activities, procedures for receiving assistance, so that this is applicable. Therefore, the existence of this family hope program assistance is still not able to improve the standard of living of young children even though policy implementers can carry out their respective main tasks and functions, and parents of early childhood have been applicable in carrying out procedures in accordance with coordination with the policy implementer.